Bee diversity in crop fields is influenced by remotely-sensed nesting resources in surrounding permanent grasslands. (July 2018) - Carrié, Romain; Lopes, Maïlys; Ouin, Annie; Andrieu, Emilie
Highlights: Two indicators of bee nest availability in permanent grasslands were assessed. They were independent from floral resources. Those two indicators were assessed at the landscape scale. Mean slope of grasslands influenced the most bee communities. Landscape-scale proportion of sparse vegetation only favored oligolectic species. Abstract: Landscape heterogeneity is an important driver of biodiversity in agroecosystems. However, the functional heterogeneity of agricultural landscapes, taking into account the different resources that habitat patches can provide to species, has rarely been studied. In this study, we explored the effect of landscape-scale nest availability provided by permanent grasslands on wild bee communities. Wild bees were sampled in 43 cereal fields in south-western France differing in the surrounding proportion of permanent grasslands. Using remote sensing tools, we measured two parameters of grassland structure known to locally influence bee nest density (slope and proportion of sparse vegetation). We found that mean slope of surrounding grasslands was the factor that most positively influenced bee richness, abundance and trait distribution in bee communities. We also found that mean slope of surrounding grasslands had a better predictive power of bee community structure than the proportion of permanent grasslands. Ground-nesting species, species with high dispersal capacities and species with a generalist diet were positively affected by the availability of sloped ground in the surrounding permanent grasslands. Only bee species with specialized flower requirements responded positively to the proportion of sparse vegetation in grasslands. Our results suggest that landscape-scale availability of nesting resources provided by grasslands affects bee communities in agricultural landscapes and can help sustain functionally diverse bee assemblages. Using simple remote sensing tools, this study highlights the importance of considering nesting resources in agricultural landscapes to maintain wild bee diversity in farmlands.